1996
DOI: 10.1007/bf01731845
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and skeletal muscle scintigraphy in dermato- and polymyositis: Clinical implications

Abstract: To determine the role of scintigraphy in the detection of skeletal and cardiac involvement in dermato- and polymyositis (DM/PM), we studied 30 patients with a confirmed diagnosis of DM/PM (23 females, 7 males; mean age: 35 years). Technetium-99m pyrophosphate (99mTc-PYP) and gallium-67 scans showed similar sensitivity, specificity and accuracy in the detection of skeletal muscle involvement when compared with serum enzymes (70%, 100% and 80%, respectively). Compared with the clinical parameters, 99mTc-PYP show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 7 publications
1
23
1
1
Order By: Relevance
“…4,8,9,13,15 The incidence of ECG abnormalities from selected articles is from 25% to 85%. 2,3,7,13,16,17 ECG and Holter abnormalities observed in PM/DM patients include: frequent atrial or ventricular premature beats, atrial tachycardia, ventricular tachycardia, atrial fibrillation, atrioventricular conduction block, bundle branch block, abnormal Q-waves, as well as nonspecific ST-T-wave changes. ST-T changes and conduction defects are the most frequent, and the occurrences are 12.5% to 56.7% and 25% to 38.5%, respectively.…”
Section: Subclinical Heart Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…4,8,9,13,15 The incidence of ECG abnormalities from selected articles is from 25% to 85%. 2,3,7,13,16,17 ECG and Holter abnormalities observed in PM/DM patients include: frequent atrial or ventricular premature beats, atrial tachycardia, ventricular tachycardia, atrial fibrillation, atrioventricular conduction block, bundle branch block, abnormal Q-waves, as well as nonspecific ST-T-wave changes. ST-T changes and conduction defects are the most frequent, and the occurrences are 12.5% to 56.7% and 25% to 38.5%, respectively.…”
Section: Subclinical Heart Involvementmentioning
confidence: 99%
“…3,24,25 There were 3.3% to 5.6% of patients who were diagnosed with old myocardial infarction by ECG. 8,17 Another 2 articles 8,25 reported myocardial infarction and remote infarction also detected in autopsied patients, and some of them were clearly related to severe coronary atherosclerosis.…”
Section: Ischemic Heart Diseasementioning
confidence: 99%
“…However, few controlled studies in patients with PM/DM have used TDI to measure LVDD (12,13); one of these studies showed significantly increased frequency of LVDD in DM patients (76.5%) versus controls (52.9%) (13). Tc-pyrophosphate ( 99m Tc-PYP) scintigraphy can be useful to detect inflammation in skeletal and cardiac muscles in patients with PM/DM (14)(15)(16). Abnormal myocardial 99m Tc-PYP uptake has been observed in 57% of a small cohort of patients with PM/DM (15).…”
Section: Introductionmentioning
confidence: 99%
“…Tc-pyrophosphate ( 99m Tc-PYP) scintigraphy can be useful to detect inflammation in skeletal and cardiac muscles in patients with PM/DM (14)(15)(16). Abnormal myocardial 99m Tc-PYP uptake has been observed in 57% of a small cohort of patients with PM/DM (15). Furthermore, myocarditis was confirmed by biopsy in patients with marked myocardial 99m Tc-PYP uptake (14).…”
Section: Introductionmentioning
confidence: 99%
“…Second, an increase in right atrial pressure usually precedes overt systolic impairment of the right ventricle, because they both decline in the last stages of decompensated right heart failure 3 . Third, an abnormal cardiac uptake during scintigraphy 4 and late gadolinium enhancement 5 has been reported for the right as well as the left ventricle in patients with IIM. Fourth, diffuse perivascular and interstitial mononuclear infiltrates, muscle fiber degeneration, and widespread fibrosis have been commonly reported in IIM autopsies 6 .…”
Section: To the Editormentioning
confidence: 94%